Glucose availability enhances lipopolysaccharide production and immunogenicity in the opportunistic pathogen Acinetobacter baumannii. (March 2016) - Rossi, Elio; Longo, Francesca; Barbagallo, Marialuisa; Peano, Clelia; Consolandi, Clarissa; Pietrelli, Alessandro; Jaillon, Sebastian; Garlanda, Cecilia; Landini, Paolo
Aim: Acinetobacter baumannii can cause sepsis with high mortality rates. We investigated whether glucose sensing might play a role in A. baumannii pathogenesis.Materials & methods: We carried out transcriptome analysis and extracellular polysaccharide determination in an A. baumannii clinical isolate grown on complex medium with or without glucose supplementation, and assessed its ability to induce production of inflammatory cytokines in human macrophages.Results: Growth in glucose-supplemented medium strongly enhanced A. baumannii sugar anabolism, resulting in increasing lipopolysaccharide biosynthesis. In addition, glucose induced active shedding of lipopolysaccharide, in turn triggering a strong induction of inflammatory cytokines in human macrophages. Finally, hemolytic activity was strongly enhanced by growth in glucose-supplemented medium.Conclusion: We propose that sensing of exogenous glucose might trigger A. baumannii pathogenesis during sepsis.